Nanometer foam metal iron-based composite material and preparation method and application thereof
By preparing nanofoam-based metal iron composite materials, the problem of low efficiency in the electroreduction of oxygen to hydrogen peroxide was solved, achieving efficient and low-cost catalyst preparation and improving the stability and catalytic activity of the catalyst.
Patent Information
- Application Number
- CN202511033922.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-11
- Filing Date
- 2025-07-25
- Publication Date
- 2025-11-04
AI Technical Summary
In existing technologies, the electroreduction of oxygen to generate hydrogen peroxide is slow, the catalyst has poor catalytic efficiency, and the preparation method is complex and costly.
A method for preparing a nanofoam metal iron-based composite material involves mixing an iron source, additives, a carbon source, and coke, followed by heat treatment and activation to form a catalyst with a nanoporous structure. Additives such as nickel, copper, calcium, and silicon regulate the crystal and electronic structures of iron, thereby enhancing catalytic activity.
It improves the efficiency of oxygen electroreduction to generate hydrogen peroxide, reduces preparation costs, simplifies the preparation process, and enhances the stability and catalytic activity of the catalyst.
Smart Images

Figure CN120888831A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of electrocatalytic oxygen reduction materials, and particularly relates to a nano-foamed metal iron-based composite material and a preparation method and application thereof. BACKGROUND
[0002] The existing hydrogen peroxide preparation method often adopts the anthraquinone method for preparation, and the process is mature, but has problems of complex unit operation, high cost and environmental pollution. The existing technology now considers electrochemical oxygen reduction to prepare H2O2, and the reaction condition is mild, environmentally friendly and low in cost, and can effectively solve the storage and transportation problems of hydrogen peroxide. Oxygen gas electro-reduction to generate hydrogen peroxide (hydrogen peroxide H2O2) mainly occurs in a two-electron oxygen reduction path (2eORR), which specifically includes: the adsorbed oxygen gas molecules are first generated *OOH through a one-step proton-electron coupling transfer (CPET) step, and then *OOH combines with protons and electrons to generate H2O2 again through a CPET step (formula 1-2);
[0003] O2+*+H + +e - →*OOH (1)
[0004] *OOH+H + +e - →H2O2 (2)
[0005] However, the generation efficiency of oxygen gas electro-reduction to generate hydrogen peroxide is slow, and the existing catalysts have poor catalytic efficiency, complex preparation method and high cost. SUMMARY
[0006] Therefore, the technical problem to be solved by the present application is to overcome the defects of slow generation efficiency of oxygen gas electro-reduction to generate hydrogen peroxide, poor catalytic efficiency of the existing catalysts, complex preparation method and high cost in the prior art, so as to provide a nano-foamed metal iron-based composite material and a preparation method and application thereof.
[0007] To this end, the present application provides the following technical solutions.
[0008] The present application provides a preparation method of a nano-foamed metal iron-based composite material, which comprises mixing an iron source, an additive, a carbon source and coke to obtain a precursor; and heat-treating and activating the precursor to obtain the nano-foamed metal iron-based composite material; and the additive comprises at least one of nickel, copper, calcium and silicon.
[0009] The nano-foamed metal iron-based composite material prepared by the present application has a nano-porous structure.
[0010] The principle of the present application is that the iron source and the coke will undergo an oxidation-reduction reaction under a heat treatment environment to generate iron and carbide, specifically as follows:
[0011] Fe x O y +mC→Fe+Fe x-1 C n-1 +CO y
[0012] wherein x is the number of atoms of iron in the iron source, y is the number of atoms of oxygen in the iron source, and m is the number of moles of carbon required to reduce 1 mole of elemental iron.
[0013] In an alternative embodiment, the iron source comprises at least one of ferrous oxide, diiron trioxide, and ferriferrous oxide; for example, a combination of ferrous oxide, diiron trioxide, a combination of ferrous oxide, ferriferrous oxide, a combination of diiron trioxide and ferriferrous oxide, a combination of ferrous oxide, diiron trioxide, and ferriferrous oxide.
[0014] In an alternative embodiment, the additive comprises at least one of a nitrate salt, a carbonate salt, and silicon dioxide.
[0015] In an alternative embodiment, the carbon source comprises at least one of acetylene black, graphite, and carbon nanotubes.
[0016] In an alternative embodiment, the length of the precursor is 2-10 cm; for example, the length of the precursor can be 2 cm, 3 cm, 4 cm, 5 cm, 6 cm, 7 cm, 8 cm, 9 cm, 10 cm, or a value within a range formed by any of the above values.
[0017] In an alternative embodiment, the ratio of the width of the precursor to the length of the precursor is (0.1-1): 1; for example, the ratio of the width of the precursor to the length of the precursor can be 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, or a value within a range formed by any of the above values.
[0018] In an alternative embodiment, the mass content of the iron source is 47-86% based on the total mass of the iron source, the additive, the carbon source, and the coke; for example, the mass content of the iron source can be 47%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 86%, or a value within a range formed by any of the above values.
[0019] In an alternative embodiment, the particle size of the iron source is 80-400 mesh; within this range, the fine particles can fill the gaps between the coarse particles, increase the bulk density, reduce the porosity, and enhance the compactness and mechanical properties of the material; for example, the physical structure of the resulting composite material is not prone to pulverization, the reaction process does not easily corrode and poison the active sites of the catalyst during the later application as a catalyst, the stable electronic structure of the electrocatalyst is maintained, and the catalytic activity and stability are improved; when the particle size of the iron source is too large, for example, the particle size of the iron source is 60 mesh, the raw materials are not uniformly mixed, and during the heat treatment and activation process, the resulting crystal grains are not uniform, which affects the formability and pressing effect of the material, causing defects and cracks in the material, and affecting the mechanical properties; when the particle size of the iron source is too small, for example, the particle size of the iron source is more than 400 mesh, the friction between the particles increases, the flowability decreases, the processing and forming of the material are affected, and thus the mechanical properties are affected; for example, the particle size of the iron source can be 80 mesh, 100 mesh, 200 mesh, 250 mesh, 300 mesh, 400 mesh, or a value within the range consisting of any of the above-mentioned values; preferably, the particle size of the iron source is 80-200 mesh; the catalytic activity and mechanical properties of the material can be further improved, thereby improving the stability of the material.
[0020] In an alternative embodiment, the mass content of the additive is 2-17% based on the total mass of the iron source, the additive, the carbon source, and the coke; for example, the mass content of the additive can be 2%, 3%, 5%, 7%, 9%, 10%, 12%, 14%, 15%, 17%, or a value within the range consisting of any of the above-mentioned values;
[0021] In an alternative embodiment, the mass content of the carbon source is 2-11% based on the total mass of the iron source, the additive, the carbon source, and the coke; for example, the mass content of the carbon source can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, or a value within the range consisting of any of the above-mentioned values;
[0022] In an alternative embodiment, the mass content of the coke is 10-25% based on the total mass of the iron source, the additive, the carbon source, and the coke; within this range, the possibility of sulfur, carbon, or other impurity elements in the coke penetrating into the iron lattice is greatly reduced, thereby improving the catalytic activity, active life, and stability of the catalyst; when the mass content of the coke is too low, for example, the mass content of the coke is 5%, the reduction of iron oxides is not complete, and iron oxides exist in the material, which affects the catalytic performance of the catalyst and thus reduces the catalytic activity; for example, the mass content of the coke can be 10%, 12%, 13%, 14%, 15%, 17%, 18%, 20%, 23%, 25%, or a value within the range consisting of any of the above-mentioned values;
[0023] In an alternative embodiment, the coke has a particle size of 80-200 mesh. If the particle size of the coke is too small, for example, if the particle size of the coke is 400 mesh, the reducing gas cannot diffuse and release in time during the reaction of the coke and the iron source, resulting in uneven local temperature distribution, affecting the growth of the catalyst crystal grains, and affecting the activity of the catalyst. For example, the particle size of the coke can be 80 mesh, 100 mesh, 125 mesh, 150 mesh, 180 mesh, 200 mesh, or a value within a range defined by any of the above values.
[0024] In an alternative embodiment, the nitrate salt includes at least one of copper nitrate and nickel nitrate.
[0025] In an alternative embodiment, the carbonate salt includes calcium carbonate.
[0026] In an alternative embodiment, the apparent density of the acetylene black is 0.2-0.3 g / cm 3 ;
[0027] In an alternative embodiment, the average particle size of the acetylene black is 20-50 nm.
[0028] In an alternative embodiment, the specific surface area of the acetylene black is 55-70 m 2 / g.
[0029] In an alternative embodiment, the iodine absorption value of the acetylene black is 60-80 g / kg.
[0030] In an alternative embodiment, the graphite has a particle size of 80-200 mesh. For example, the particle size of the graphite can be 80 mesh, 100 mesh, 125 mesh, 150 mesh, 180 mesh, 200 mesh, or a value within a range defined by any of the above values.
[0031] In an alternative embodiment, the heat treatment is performed under a protective atmosphere.
[0032] Preferably, the protective atmosphere includes at least one of an inert atmosphere and a nitrogen atmosphere.
[0033] Preferably, the inert atmosphere includes at least one of argon and helium.
[0034] In an alternative embodiment, the temperature of the heat treatment is 900-1350°C; when the temperature of the heat treatment is too high, for example, the temperature of the heat treatment is 1400°C, it can cause the sintering of the grains of the iron catalyst, and in addition, it can introduce new impurity elements, thereby reducing the catalytic activity of the material; when the temperature of the heat treatment is too low, for example, the temperature of the heat treatment is 800°C, it can cause the reduction process to be insufficient, thereby reducing the catalytic activity of the material; the temperature of the heat treatment according to the present application can sufficiently reduce the iron oxides, thereby improving the electronic conductivity of the nanofoam metal iron-based composite material and improving the catalytic activity of the electrocatalyst; the adjustment of the temperature can achieve the regulation of the physical structure and the surface chemical state of the catalyst, and it can play a positive role in the adsorption, diffusion and reaction of oxygen in the oxygen electroreduction process; the temperature of the heat treatment of the prior art catalytic material is too low, which can cause the incomplete reduction of the iron oxides, thereby causing poor electronic conductivity; in addition, the adsorption of the iron oxides on oxygen and intermediate products is too strong, which is not conducive to the exposure of the active sites of the catalyst, thereby causing poor catalytic activity of the material; for example, the temperature of the heat treatment can be 900°C, 1000°C, 1050°C, 1100°C, 1200°C, 1300°C, 1350°C, or a value within a range consisting of any of the aforementioned values; preferably, the temperature of the heat treatment is 950-1150°C; the nanofoam metal iron-based composite material prepared in the preferred temperature range has better catalytic efficiency.
[0035] In an alternative embodiment, the time of the heat treatment is 1-5h; when the time of the heat treatment is too long, for example, the time of the heat treatment is 6h, it can cause the sintering of the grains of the catalyst, thereby reducing the catalytic activity of the material; when the time of the heat treatment is too short, for example, the time of the heat treatment is 0.5h, it can cause the incomplete growth of the grains of the catalyst, thereby causing poor stability of the catalyst; for example, the time of the heat treatment can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or a value within a range consisting of any of the aforementioned values; preferably, the time of the heat treatment is 2-4h; the nanofoam metal iron-based composite material prepared in the preferred time range has better catalytic efficiency.
[0036] In an alternative embodiment, the activation is activated by an acid solution.
[0037] In an alternative embodiment, the acid solution comprises at least one of a hydrochloric acid solution, a sulfuric acid solution, an oxalic acid solution and an acetic acid solution;
[0038] In an alternative embodiment, the concentration of the acid solution is 0.2-6mol / L; for example, the concentration of the acid solution can be 0.2mol / L, 1mol / L, 2mol / L, 3mol / L, 4mol / L, 5mol / L, 6mol / L, or a value within a range consisting of any of the aforementioned values.
[0039] In an alternative embodiment, the activation time is 1-6h. For example, the activation time can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 5h, 6h, etc. or a value within a range consisting of any of the aforementioned values.
[0040] In an alternative embodiment, the mixing further comprises adding a solvent to obtain a mixed slurry, and kneading the mixed slurry into the precursor;
[0041] Preferably, the structure of the precursor comprises a strip, a sphere, a spheroid; the spheroid is a long rotating spheroid;
[0042] Preferably, the strip comprises a cylinder;
[0043] When the precursor is a strip, the length of the precursor refers to the maximum linear dimension in the long axis direction; the width of the precursor refers to the maximum linear dimension in the short axis direction;
[0044] Further, when the precursor is a cylinder, the length of the precursor refers to the maximum linear dimension in the axis direction; the width of the precursor refers to the diameter of the cross section;
[0045] When the precursor is a sphere, the length of the precursor refers to the diameter; the width of the precursor refers to the diameter;
[0046] When the precursor is a spheroid, the length of the precursor refers to the maximum linear dimension in the long axis direction; the width of the precursor refers to the maximum linear dimension in the short axis direction;
[0047] Preferably, the solvent comprises water.
[0048] In an alternative embodiment, after the heat treatment, the method further comprises cooling to room temperature, and then activating;
[0049] Preferably, the cooling rate is 2-5℃ / min;
[0050] In an alternative embodiment, after the activation, the method further comprises cleaning and / or drying;
[0051] Preferably, the solution for cleaning comprises water.
[0052] The application also provides a nanofoam metal iron-based composite material, which is prepared according to the above preparation method.
[0053] Preferably, the length of the nanofoam metal iron-based composite material is 2-10cm;
[0054] Preferably, the specific surface area of the nanofoam metal iron-based composite material is 2-20m2 / g;
[0055] Preferably, the pore size distribution range of the nanometer foam metal iron-based composite material is 10-100nm;
[0056] Preferably, the average pore size of the nanometer foam metal iron-based composite material is 20-30nm;
[0057] Preferably, the pore volume of the nanometer foam metal iron-based composite material is 0.1-0.4cm 3 / g.
[0058] When the current driver is a strip, the length of the nanometer foam metal iron-based composite material refers to the maximum linear size in the long axis direction;
[0059] Further, when the current driver is a cylindrical shape, the length of the nanometer foam metal iron-based composite material refers to the maximum linear size in the axial direction;
[0060] When the current driver is a spherical shape, the length of the nanometer foam metal iron-based composite material refers to the diameter;
[0061] When the current driver is a rugby ball shape, the length of the nanometer foam metal iron-based composite material refers to the maximum linear size in the long axis direction;
[0062] The application also provides an application of the nanometer foam metal iron-based composite material prepared by the above preparation method in a catalyst;
[0063] Preferably, the nanometer foam metal iron-based composite material is used as a hydrogen peroxide catalyst.
[0064] The technical scheme of the application has the following advantages:
[0065] 1.The preparation method of the nanometer foam metal iron-based composite material provided by the application, wherein an iron source, an additive, a carbon source and coke are mixed to obtain a precursor; the precursor is heat treated and activated to obtain the nanometer foam metal iron-based composite material; the additive elements of the additive include at least one of nickel, copper, calcium and silicon. The nanometer foam metal iron-based composite material provided by the application has high catalytic activity and high stability; the preparation method is simple, and the raw material cost is low. The additive can control the temperature of iron reduction, and the elements in the additive, such as nickel, copper, calcium and silicon, can produce rich heterogeneous structures due to the difference in the melting and boiling points of iron alloys, and at the same time in the heat treatment process, the additive elements of the additive can affect the crystal structure of iron, introduce more defect sites, and perform electronic structure regulation to improve the performance of the nanometer foam metal iron-based composite material in catalytic reduction to generate hydrogen peroxide, thereby improving the catalytic activity, efficiency and catalytic stability. The coke reduces the iron source to low-valence elemental iron and carbonized iron in the heat treatment process, and a small amount of organic matter contained in the coke will also undergo reduction and polymerization reactions in the heat treatment process, which not only produces nanopores but also forms graphitized carbon microcrystals, which is beneficial to improving the electrocatalytic oxygen reduction rate of the composite material.
[0066] 2.The preparation method of the nanometer foam metal iron-based composite material provided by the application, wherein the carbonates decompose to produce carbon dioxide in the heat treatment process, and the heat treatment can produce a nanoporous structure rich in gas, and more nanoporous structures can be further produced in the activation process; thereby strengthening the adsorption, diffusion and mass transfer processes of oxygen, and further improving the oxygen reduction performance; the silicon dioxide can produce rich nanoporous structures in the activation process, thereby improving the oxygen reduction performance. The nitrate can improve the adsorption and desorption energy barrier of the catalyst surface to oxygen and intermediates, which is beneficial to improving the electrochemical performance. BRIEF DESCRIPTION OF DRAWINGS
[0067] In order to more clearly illustrate the specific embodiments of the present application or the technical solutions in the prior art, the drawings needed in the following specific embodiments or prior art description will be briefly introduced. Obviously, the drawings in the following description are some embodiments of the present application, and other drawings can also be obtained by those skilled in the art without creative labor.
[0068] Figure 1 is the XRD diffraction pattern of the nanometer foam metal iron-based composite material prepared in Example 1 and Example 4 (the abscissa is the diffraction angle, and the ordinate is the diffraction intensity). DETAILED DESCRIPTION
[0069] The following examples are provided to better enable those skilled in the art to which the application pertains to further understand the application and are not intended to limit the scope of the application, which is defined by the appended claims. Any product that is the same as or similar to the present application derived from the disclosure of the present application or from the combination of the present application with other prior art features falls within the scope of the present application.
[0070] When the specific experimental steps or conditions are not mentioned in the examples, the operations or conditions can be carried out according to the conventional experimental steps described in the literature in the art. When the manufacturers of the reagents or instruments are not mentioned, the reagents are conventional reagent products that can be obtained by purchase in the market.
[0071] The present application provides a preparation method of a nano-foamed metal iron-based composite material, comprising the following steps:
[0072] With the total mass of the iron source, the additive, the carbon source and the coke as the reference, 47-86% of the iron source, 2-17% of the additive, 2-11% of the carbon source and 10-25% of the coke are mixed to obtain a mixed slurry by adding a solvent (for example, water), and the mixed slurry is kneaded to obtain a precursor. A granulator or a molding machine is used in the kneading process. The structure of the precursor includes a strip body, a spherical body and a spheroid body. The strip body includes a cylindrical body. After heat treatment, cooling, activation and cleaning, the precursor is dried to obtain the nano-foamed metal iron-based composite material.
[0073] Example 1
[0074] The present application provides a preparation method of a nano-foamed metal iron-based composite material, comprising the following steps:
[0075] With the total mass of the iron source, the additive, the carbon source and the coke as the reference, 47-86% of the iron source, 2-17% of the additive, 2-11% of the carbon source and 10-25% of the coke are mixed to obtain a mixed slurry by adding a solvent (for example, water), and the mixed slurry is kneaded to obtain a precursor. A granulator or a molding machine is used in the kneading process. The structure of the precursor includes a strip body, a spherical body and a spheroid body. The strip body includes a cylindrical body. After heat treatment, cooling, activation and cleaning, the precursor is dried to obtain the nano-foamed metal iron-based composite material. 2 3 / g; the average pore size is 29 nm, and the pore size distribution range is 10-100 nm; the pore volume is 0.16 cm 3 / g.
[0076] The XRD diffraction spectrum of the nano-foamed metal iron-based composite material of Example 1 is shown in FIG. 1. Figure 1It can be seen that the diffraction peak of the nanometer foam metal iron-based composite material provided in the embodiment is weak and has a large drift, indicating that the crystal structure of the material is amorphous, and the diffraction peaks of Fe are at 2θ = 44.3°, 64.4° and 82.0°, and the diffraction peak of FeC alloy is at 2θ = 43.3°, indicating that the main element composition of the material is Fe.
[0077] Example 2
[0078] The embodiment provides a preparation method of a nanometer foam metal iron-based composite material, and the method comprises the following steps:
[0079] In mass percentage, 20% of 200-mesh ferrous oxide, 45% of 200-mesh ferric oxide, 7% of silicon dioxide, 3% of acetylene black and 25% of 180-mesh coke are mixed, water is added to obtain a mixed slurry, the mixed slurry is kneaded into a cylindrical precursor in a granulator, the length of the precursor is 3 cm, and the width of the precursor is 2 cm; under the protection of argon and helium atmospheres, the precursor is heat-treated at 1000 DEG C for 5 h, cooled to room temperature at a cooling rate of 4 DEG C / min, activated by using a 1.5 mol / L hydrochloric acid solution for 5 h, washed with deionized water until neutral, dried, and a nanometer foam metal iron-based composite material is obtained. The nanometer foam metal iron-based composite material has a length of 2.6 cm, a specific surface area of 18 m 2 / g, an average pore size of 21 nm, and a pore size distribution range of 10-100 nm; and a pore volume of 0.24 cm 3 / g.
[0080] The apparent density of the acetylene black is 0.2-0.3 g / cm 3 ; the average particle size is 20 nm; the specific surface area is 55-70 m 2 / g; and the iodine absorption value is 60-80 g / kg.
[0081] Example 3
[0082] The embodiment provides a preparation method of a nanometer foam metal iron-based composite material, and the method comprises the following steps:
[0083] In mass percentage, 33% of 200-mesh ferriferrous oxide, 25% of 200-mesh ferric oxide, 15% of calcium carbonate, 11% of acetylene black and 16% of 80-mesh coke are mixed, water is added to obtain a mixed slurry, the mixed slurry is kneaded into a spherical precursor in a molding machine, and the diameter of the spherical precursor is 4 cm; under the protection of nitrogen atmosphere, the precursor is heat-treated at 1050 DEG C for 4 h, cooled to room temperature at a cooling rate of 3 DEG C / min, activated by using a 0.5 mol / L hydrochloric acid solution for 4 h, washed with deionized water until neutral, dried, and a nanometer foam metal iron-based composite material is obtained. The nanometer foam metal iron-based composite material has a length of 3.6 cm, a specific surface area of 20 m 2 / g; average pore size is 15 nm, pore size distribution range is 10-100 nm; pore volume is 0.34 cm 3 / g.
[0084] The apparent density of acetylene black is 0.2-0.3 g / cm 3 ; average particle size is 50 nm; specific surface area is 55-70 m 2 / g; iodine absorption value is 60-80 g / kg.
[0085] Example 4
[0086] The present embodiment provides a preparation method of a nano foam metal iron-based composite material, comprising the following steps:
[0087] 9% of 200 mesh ferrous oxide, 28% of 200 mesh ferriferrous oxide, 27% of 200 mesh ferrous oxide, 6% of nickel nitrate, 6% of calcium carbonate, 6% of acetylene black, 4% of 200 mesh graphite powder and 14% of 150 mesh coke are mixed in mass percentage, and water is added to obtain a mixed slurry. The mixed slurry is kneaded into an olive ball-shaped precursor in a molding machine. The length of the precursor is 6 cm, and the width of the precursor is 5 cm. Under a nitrogen atmosphere, the precursor is heat treated at 1250°C for 2 h, cooled to room temperature at a cooling rate of 3°C / min, activated with 1 mol / L hydrochloric acid solution for 2 h, washed with deionized water until neutral, dried, and a nano foam metal iron-based composite material is obtained. The length of the nano foam metal iron-based composite material is 4.8 cm; the specific surface area is 20 m 2 / g; the average pore size is 23 nm, the pore size distribution range is 10-100 nm; the pore volume is 0.28 cm 3 / g.
[0088] The apparent density of acetylene black is 0.2-0.3 g / cm 3 ; average particle size is 30 nm; specific surface area is 55-70 m 2 / g; iodine absorption value is 60-80 g / kg.
[0089] The XRD diffraction pattern of the nano foam metal iron-based composite material of Example 4 is shown in Figure 1 It can be seen that the diffraction peak of the nano foam metal iron-based composite material provided in the present embodiment is weak and has a large drift, indicating that the crystal structure of the material is amorphous. The diffraction peaks at 2θ = 44.3°, 64.4° and 82.0° are Fe diffraction peaks, and the diffraction peak at 2θ = 43.3° is a FeC alloy diffraction peak, indicating that the main element composition of the material is Fe.
[0090] Example 5
[0091] The present embodiment provides a preparation method of a nano foam metal iron-based composite material, comprising the following steps:
[0092] By mass percentage, 25% of 200-mesh ferric oxide, 25% of 200-mesh ferric oxide, 15% of copper nitrate, 10% of carbon nanotubes, and 25% of 120-mesh coke were mixed, and water was added to obtain a slurry. The slurry was then kneaded into spherical precursors with a diameter of 4 cm in a molding machine. The precursors were heat-treated at 1050℃ for 4 hours under a nitrogen atmosphere, cooled to room temperature at a cooling rate of 4℃ / min, activated with 1 mol / L acetic acid solution for 4 hours, washed with deionized water until neutral, and dried to obtain a nanofoam metal-iron-based composite material. The nanofoam metal-iron-based composite material has a length of 3.9 cm and a specific surface area of 13 m². 2 / g; average pore size is 22nm, pore size distribution range is 10-100nm; pore volume is 0.35cm³. 3 / g.
[0093] Example 6
[0094] This embodiment provides a method for preparing nanofoam metal iron-based composite materials, including the following steps:
[0095] By mass percentage, 9% ferrous oxide (200 mesh), 28% magnetite (200 mesh), 27% ferric oxide (200 mesh), 6% nickel nitrate, 6% calcium carbonate, 6% acetylene black, 4% graphite powder (200 mesh), and 14% coke (150 mesh) were mixed, and water was added to obtain a slurry. The slurry was then kneaded into rugby ball-shaped precursors in a molding machine. The precursors were 6 cm long and 5 cm wide. The mixture was heat-treated at 1100℃ for 2 hours under a nitrogen atmosphere, cooled to room temperature at a cooling rate of 3℃ / min, activated with 1 mol / L hydrochloric acid solution for 2 hours, washed with deionized water until neutral, and dried to obtain a nanofoam metal-iron-based composite material. The nanofoam metal-iron-based composite material had a length of 5 cm and a specific surface area of 13 m². 2 / g; average pore size is 25nm, pore size distribution range is 10-100nm; pore volume is 0.24cm³. 3 / g.
[0096] The apparent density of acetylene black is 0.2-0.3 g / cm³. 3 Average particle size: 30 nm; specific surface area: 55-70 m² 2 / g; Iodine uptake value is 60-80g / kg.
[0097] Comparative Example 1
[0098] This comparative example provides a method for preparing an iron-based composite material, which differs from Example 1 only in that no additives are added.
[0099] Comparative Example 2
[0100] The comparative example provides a preparation method of the iron-based composite material, and the difference compared with example 1 is only that no coke is added.
[0101] Comparative example 3
[0102] The comparative example provides a preparation method of the iron-based composite material, and the difference compared with example 1 is only that no coke is added.
[0103] Test example
[0104] The nanofoam metal iron-based composite materials prepared in examples 1-6 and the iron-based composite materials prepared in comparative examples 1-3 are placed in a 0.25 mol / L sodium sulfate solution, oxygen is introduced into the solution, the concentration of oxygen is kept saturated, the stirring speed of the solution is 500-1500 rpm, the pH value of the solution is 2-5, the reacted solution is titrated by using cerium sulfate through the oxidation-reduction titration method to determine the hydrogen peroxide, and the generation rate of hydrogen peroxide (H2O2) is shown in Table 1.
[0105] Table 1
[0106]
[0107]
[0108] As can be seen from Table 1, the nanofoam metal iron-based composite material prepared by the present application catalyzes the generation of hydrogen peroxide, and significantly improves the generation rate of hydrogen peroxide.
[0109] Obviously, the above examples are only examples for clearly illustrating, and are not limitation to the embodiments. Other different forms of changes or variations can be made on the basis of the above description for ordinary skilled in the art. All the embodiments need not and cannot be exhausted here. The obvious changes or variations derived therefrom are still within the protection scope of the present application.
Claims
1. A method for preparing a nanofoam metal-iron-based composite material, characterized in that, Iron source, additives, carbon source and coke are mixed to obtain the precursor; Heat treatment and activation yield nanofoam metal-based composite material; the additives include at least one of nickel, copper, calcium, and silicon.
2. The preparation method according to claim 1, characterized in that, The iron source includes at least one of ferrous oxide, ferric oxide, and magnetite; and / or, The additive includes at least one of nitrates, carbonates, and silica; and / or, The carbon source includes at least one of acetylene black, graphite, and carbon nanotubes; and / or, The precursor is 2-10 cm in length; and / or, The ratio of the width to the length of the precursor is (0.1-1):
1.
3. The preparation method according to claim 1 or 2, characterized in that, Based on the total mass of the iron source, additives, carbon source, and coke, the iron source has a mass content of 47-86%; and / or, The iron source has a particle size of 80-400 mesh; preferably, the iron source has a particle size of 80-200 mesh; and / or, Based on the total mass of the iron source, additives, carbon source, and coke, the mass content of the additives is 2-17%; and / or, Based on the total mass of iron source, additives, carbon source, and coke, the mass content of the carbon source is 2-11%; and / or, Based on the total mass of iron source, additives, carbon source, and coke, the mass content of said coke is 10-25%; and / or, The coke has a particle size of 80-200 mesh.
4. The preparation method according to claim 2 or 3, characterized in that, The nitrate includes at least one of copper nitrate and nickel nitrate; and / or, The carbonate includes calcium carbonate; and / or, The apparent density of the acetylene black is 0.2-0.3 g / cm³. 3 ; and / or, The acetylene black has an average particle size of 20-50 nm; and / or, The specific surface area of the acetylene black is 55-70 m². 2 / g; and / or, The acetylene black has an iodine absorption value of 60-80 g / kg; and / or, The graphite has a particle size of 80-200 mesh.
5. The preparation method according to any one of claims 1-4, characterized in that, The heat treatment is performed under a protective atmosphere; and / or, The heat treatment temperature is 900-1350℃; and / or, The heat treatment time is 1-5 hours; and / or, The activation is performed using an acid solution.
6. The preparation method according to any one of claims 1-5, characterized in that, The protective atmosphere includes at least one of an inert atmosphere and a nitrogen atmosphere; preferably, the inert atmosphere includes at least one of argon and helium; and / or, The heat treatment temperature is 950-1150℃; and / or, The heat treatment time is 2-4 hours; and / or, The acid solution includes at least one selected from hydrochloric acid solution, sulfuric acid solution, oxalic acid solution, and acetic acid solution; and / or, The concentration of the acid solution is 0.2-6 mol / L; and / or, The activation time is 1-6 hours.
7. The preparation method according to any one of claims 1-6, characterized in that, The mixing process also includes adding a solvent to obtain a mixed slurry, and kneading the mixed slurry into a precursor; Preferably, the precursor structure includes strips, spheres, and olive-shaped bodies; Preferably, the strip comprises a cylinder; Preferably, the solvent includes water.
8. The preparation method according to any one of claims 1-7, characterized in that, The heat treatment further includes cooling to room temperature followed by activation; preferably, the cooling rate is 2-5°C / min; and / or, The activation process also includes cleaning and / or drying, and preferably, the cleaning solution includes water.
9. A nanofoam metal-iron-based composite material, characterized in that, Nanofoam metal-iron-based composite materials prepared according to any one of claims 1-8; Preferably, the length of the nanofoam metal-iron-based composite material is 2-10 cm; Preferably, the specific surface area of the nanofoam metal-iron-based composite material is 2-20 m². 2 / g; Preferably, the pore size distribution range of the nanofoam metal iron-based composite material is 10-100 nm; Preferably, the average pore size of the nanofoam metal-based composite material is 20-30 nm; Preferably, the pore volume of the nanofoam metal-based composite material is 0.1-0.4 cm³. 3 / g.
10. The application of the nanofoam metal iron-based composite material prepared by the preparation method according to any one of claims 1-8 in a catalyst; Preferably, the nanofoam metal iron-based composite material is used as a catalyst for preparing hydrogen peroxide.